Portfolio Diversification Opportunities On The Asean 5 Stock Market And Sectoral Stock Indexes On The Indonesian Stock Exchange - Rahmat Budi Santoso; Erawati Kartika; Ika Listyawati (International Conference On Digital Advanced Tourism Management And Technology, 2023)
This study aims to examine portfolio diversification opportunities on the stock markets of Indonesia, Singapore, Malaysia, Thailand, and the Philippines, as well as sectoral stock price indices on the Indonesian Stock Exchange. The data used is the closing daily price index for the period January 2021 – October 2023. The analysis method uses principal component analysis. The results show that the first forming component includes the Indonesian stock market and its sectoral stock price index. The second component is filled by the stock markets of Singapore, Malaysia, Thailand, and the Philippines. The third component is the consumer goods cyclical and technology sector, then the fourth component is the consumer goods non-cyclical and healthcare sector. Based on the research results, it shows that there are differences in return variance between the five stock markets on ASEAN 5 and the sectoral stock price index on the Indonesia Stock Exchange. Investors can diversify their portfolios into other countries stock markets that have a low correlation with the domestic stock market. This also helps investors outside Indonesia to look for opportunities to diversify into various stock sectors on the Indonesian stock exchange, even though the opportunities are limited.